Service quality and consumer trust as determinants of customer satisfaction: Evidence from an automotive showroom in Medan - Desma Erica Maryati Manik; Isra Rafika Sihombing; Dian Setyorini; Rima Sapira; Sri Rezeki (Pusat P2M Politeknik Negeri Batam, 2026)
Consumer satisfaction in the automotive retail sector is shaped by both operational and relational service factors, yet empirical evidence integrating these mechanisms in the Indonesian two-wheeler showroom context remains scarce. Against a backdrop of year-to-year sales variation at Yamaha Motor Showroom Branch Klambir V in the Medan–Deli Serdang corridor, this study examines the effects of service quality and consumer trust on customer satisfaction. A quantitative cross-sectional survey design was employed with 150 respondents selected through purposive sampling. Data were collected using a structured questionnaire measured on a five-point Likert scale. Instrument validity was assessed via Corrected Item-Total Correlation and reliability via Cronbach’s Alpha; classical assumption tests (normality, multicollinearity, and heteroskedasticity) preceded multiple linear regression. All instruments were valid and reliable (α > 0.80). Regression results indicated that service quality (β = 0.497, t = 8.121, p < 0.001) and consumer trust (β = 0.473, t = 7.734, p < 0.001) each exerted a positive and significant effect on customer satisfaction, and jointly explained 44.3% of its variance (F = 60.186, p < 0.001, Adjusted R² = 0.443). Theoretically, the study extends the SERVQUAL and commitment–trust frameworks by demonstrating that an operational construct (service quality) and a relational construct (trust) function as comparably strong, complementary determinants of satisfaction within a single bounded automotive-retail setting—a context in which the two have rarely been tested jointly. Practically, management is advised to invest in service training, strengthen the service environment, and improve communication transparency to sustain consumer trust and satisfaction.